Patella fractures are not associated with an increased risk of mortality in elderly patients. Issue 10 (October 2018) - Larsen, Peter; Elsoe, Rasmus
Abstract: Introduction: The modern literature includes only limited information regarding mortality rates and cumulative survival following patella fractures. The aim was to report the 30-day, six-month, and one-year mortality of patients with patella fractures and compare this to the mortality of a matched reference population. Methods: All patients who sustained a patella fracture in Denmark between 1996 and 2000 were included in the study. The survival status of these patients was monitored until 2015. We compare the mortality with a ten-fold reference population matched on age and gender without a prior patella fracture. Results: 6096 patients were treated for 6114 patella fractures. The mean age of patients was 48.9 years. The overall mortality rates at 30 days, six months, and one year were 0.7%, 1.8%, and 2.8%. The mortality rates for patients > 65 years at 30 days, six months, and one year were 1.3%, 3.9%, and 6.2%. The mortality rates for patients at ≤ 65 years at 30 days, six months, and one year were 0.4%, 0.9%, and 1.3%. Compared to the matched reference population, the relative risk of mortality in patients > 65 years at 30 days, six months, and one year were 1.9 (95% CI 1.2–2.9), 1.0 (95% CI 0.8–1.3), and 0.9 (95% CI 0.7–1.1). Conclusion: The overall one-year mortality rate of patella fractures was 2.8% and this was increased to 6.2% in patients older than 65 years. In elderly patients above 65 years, the relative risk of death was 0.9, indicating that patella fractures in elderly patients were not associated with an increased mortality rate.